Cardiovascular Mortality after Venous Thromboembolism: A Meta-Analysis of Prospective Cohort Studies - Noumegni, Steve Raoul; Grangereau, Thomas; Demir, Arzu; Bressollette, Luc; Couturaud, Francis; Hoffmann, Clément (Seminars in Thrombosis and Hemostasis, 2021)
Many studies from current literature show that cardiovascular diseases in patients with venous thromboembolism (VTE) are more frequent than in the general population without VTE. However, data summarizing the impact of cardiovascular diseases on mortality of patients with VTE are lacking. In this systematic review and meta-analysis, we aimed to determine the frequency and incidence rate of cardiovascular death in patients with VTE. MEDLINE and EMBASE were searched from January 1, 2000 to February 28, 2021. Eligible studies were observational prospective cohort studies including patients with VTE and reporting all causes of death. Cardiovascular death was defined as deaths that result from new or recurrent pulmonary embolism, death due to acute myocardial infarction, sudden cardiac death or heart failure, death due to stroke, death due to cardiovascular procedures or hemorrhage, death due to ruptured aortic aneurysm or aortic dissection and death due to other cardiovascular causes. Random-effect models meta-analysis served to determine all pooled effect size of interest with their 95% confidence interval (CI). Thirteen observational studies enrolling 22,251 patients were identified and included. The mean/median age varied between 49 and 75 years. The proportion of men ranged from 38.3 to 53.2%. The overall pooled frequency of cardiovascular death in patients with VTE was 3.9% (95% CI: 2.5–5.6%), while the overall pooled frequency of all-cause mortality was 12.0% (95% CI: 9.1–15.4%). The pooled proportion of cardiovascular death among all causes of deaths in patients with VTE was 35.2% (95% CI: 22.2–49.3%). The pooled incidence rate of cardiovascular death was 1.92 per 100 patient-years (95% CI: 0–4.1). The frequency of cardiovascular death in patients with VTE was significantly higher than in patients without VTE (risk ratio: 3.85, 95% CI: 2.75–5.39). Based on this updated meta-analysis from 13 prospective cohort studies, cardiovascular death in patients with VTE is more frequent than in the general population without VTE.
Keywords: cardiovascular mortality; cardiovascular death; venous thromboembolism; frequency; incidence; meta-analysis